Analysis of the Impact of Reclamation on Water Level Rise and Sedimentation - Mahardika Yogatama - NIM : 25515003 , Gema
The Jakarta Beach Reclamation is the most talked about issue in the last 2 years. However, the environmental impacts are feared if 17 reclamation islands are completed, there is still no deep study that can be publicized. The process of rising the water level at the river estuary and sedimentation will be modeled using Delft3D where begun with large area simulation that contains Java island, Sumatera and Kalimantan, and its results will be calibrated by 4 (four) tidal stations and 1 (one) current station that are Dishidros data. Next step is simulation of small area in Jakata Bay. This small area model will be calibrated by 3 field data of tidal stations in October 2015 period. Both process will be analyzed until got smallest error margin of calibration Water level rise of Estuary will be simulated in 7 (seven) rivers in Jakarta Bay, with 5 engneering scenarios of 17 reclamation islands dan beeing analyzed comparison of water level rise in each rivers. In the Delft3D sedimentation simulation will be done with daily river discharge input and wave height for one year and with two scenarios of wave direction. Final results of all its simulation is to get sedimentation rate especially in the gap of each reclamation island.